Ecoprint; Pemanfaatan Bahan Alam Sebagai Peningkatan Pengetahuan dan Kreativitas Siswa Di SDN Reusak Samatiga, Aceh Barat - Maulida, Ulvia; Khairi, Jamadil; Rahmi, Rina; Ramazan, Nova; Amni, Maulidil; Nadya; Rahmah, Siti; Safitri, Ema; Wulandari, Sri (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
Creativity is one of the potentials of children that must be developed from birth. Awareness of the surrounding environment can help students understand the opportunities that exist and encourage them to think creatively in utilizing available resources. SDN Reusak School is the first foundation in the cultivation of skills, therefore the activity was carried out at SDN Reusak School. In the context of education, ecoprint training can be an innovative tool to stimulate students' creativity. In this Community Service activity by providing training and education on how to make artwork using ecoprint techniques. The implementation of ecoprint training and education activities is expected to provide benefits in the future. The method of activities carried out includes preparation, counseling, and demonstration. The results achieved were that students of SDN Reusak, Samatiga sub-district gained new insights and skills in an effort to utilize natural materials around the environment to produce ecoprint products with unique designs according to their respective creativity.